HUBUNGAN TINGKAT KETERGANTUNGAN DAN TINGKAT STRES PASIEN STROKE AKUT RAWAT INAP - Daniella Natasya; Budi Riyanto Wreksoatmodjo; Mahaputra Mahaputra (NEURONA, 2021)
Introduction: Stroke is the second leading cause of death worldwide and the leading cause of disability in adults. Disability will affect functional abilities in activities of daily living which can lead to mental health issues, for example, psychological stress. Aim: This study aims to determine the relationship between the level of dependence and the level of stress in hospitalized acute stroke patients Methods: A cross-sectional analytic study was conducted on 64 respondents of acute stroke patients hospitalized at Atma Jaya Hospital and Izza Hospital from November 2020-March 2021. The level of ADL dependence was determinedusing the Barthel Index questionnaire, and the stress level was determined using the DASS-42 questionnaire. Data analysis using Chi-square test with alternative Kruskal Wallis test. Results: Most respondents were male (59.4%) and aged ≥ 59 years (62.5%). The majority have a moderate level of dependence (42.2%) and experience moderate stress (39.1%). There is a relationship between the level of dependence and the stress level with a p<0.05. Discussion: Limitations in daily activities caused by a stroke can cause stress. Untreated, prolonged stress can lead to more serious mental health disorders. Families and nurses need to carry out psychological management to improve the quality of life of stroke survivors. Keywords: Acute stroke, ADL, dependency level, stress level